Model Pemberdayaan Ekonomi Umat Melalui Aset Wakaf Masjid Besar Darul Muttaqin Kecamatan Alang Alang Lebar Palembang - Syukriah, Syukriah; Antasari, Rina; Azwari, Peny Cahaya (Jurnal Iqtisaduna, 2024)
This research aims to describe the model of economic empowerment of the people through the waqf assets of the Darul Muttaqin Grand Mosque. The research problem is to find out the description of the model, analysis and transformation of economic empowerment of the people through waqf assets at the Darul Muttaqin Grand Mosque, Alang Alang Lebar District. The research method the author uses is qualitative. Based on the results of the research and discussion, it is known that the description of the economic empowerment model for the people is a consumptive model and a productive model which is useful in assisting in poverty alleviation programs and leading to a prosperous society by empowering an independent community economy. Useful for increasing economic welfare, helping to increase community income, economic independence and reducing poverty, and for economic empowerment of the people based on sharia values in congregation, carried out based on cooperation and based on the spirit of helping each other in goodness, and can be transformed into the community or congregation appropriate and in accordance with Islamic law.